EVALUATION OF BIO-CORROSION ON CARBON STEEL BY BACILLUS MEGATERIUM IN BIODIESEL AND DIESEL OIL MIXTURE - Pusparizkita, Yustina Metanoia; Schmahl, Wolfgang; Setiadi, Tjandra; Ilsemann, Bork; Reich, Mike; Devianto, Hary; Harimawan, Ardiyan (Journal of Engineering and Technological Sciences, 2020)
Biodiesel can act as carbon source for bacterial metabolisms, leading to corrosion of carbon steel. In this study, the corrosion of carbon steel by biodiesel blends (B15, B20, B30) was observed in the presence of Bacillus megaterium. The effect of biodiesel concentration on microorganism-induced corrosion was investigated by electrochemical impedance spectroscope (EIS), scanning electron microscope (SEM) and digital microscope. The results showed that under various biodiesel concentrations, Bacillus megaterium can grow and form biofilm on carbon steel. Based on the impedance analysis, their presence can increase the corrosion rate and cause pitting corrosion because the biofilm can change the electrochemical reactions in the metal or the interface solution and the kinetics of the anodic cathodic reactions. Also, Bacillus megaterium produces acid metabolites and can oxidize iron. Besides being influenced by Bacillus megaterium activities, the pitting formed on carbon steel depends on the biodiesel concentration. The results showed a great deal of shallow pit formation in B30, exacerbating the severity of metal roughness.